Regional risk factors associated with adverse outcomes of COVID-19 infection among the older adult: A systematic review and meta-analysis - Olunike Rebecca Abodunrin; Mobolaji Timothy Olagunju; Xinyi Huang; Jianming Wang; Zhibin Hu; Chong Shen (Journal of Infection and Public Health)
The rapid global spread of Coronavirus Disease 2019 (COVID-19) has resulted in millions of infections and deaths, particularly impacting older adults. This study systematically analyzes risk factors reported in different geographical regions such as Asia and Europe that are associated with adverse outcomes in older adults with COVID-19. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we searched five databases up to December 2023 and conducted meta-analyses of odds ratios for 27 risk factors reported in at least two studies using R software (version 4.3.2). Our meta-analysis identified 19 risk factors linked to adverse outcomes, with many of them common across regions, particularly in Asia and Europe. Key factors include old age (above 65 years), male gender, symptoms such as fever and dyspnea, and comorbidities like dementia, chronic obstructive pulmonary disease (COPD), chronic heart disease, hypertension, chronic kidney disease, and malnutrition. Laboratory biomarkers such as low oxygen saturation, thrombocytopenia, and elevated D-dimer were also associated with adverse outcomes. COVID-19 patients in Asia and Europe who are older adults, male, or have specific symptoms combined with underlying health conditions are at an increased risk of progressing to severe illness or mortality.